ФЕНОМЕН ТІЛЕСНОСТІ ТА ЇЇ СОЦІОКУЛЬТУРНІ РЕПРЕЗЕНТАЦІЇ В УКРАЇНСЬКІЙ ТА ЯПОНСЬКІЙ КУЛЬТУРІ - Дубовенко, Н. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Людська тілесність як соціально-філософська проблема постійно приваблювала цікавість: як тілесні сили розкриваються в житті та соціальному бутті людини, якими є взаємозв’язки тіла, душі та духу та чи є межі їх розвитку. Феномен тілесності та її соціокультурні репрезентації в українській та японській культурі в достатній мірі нова та малодосліджена тема. Технократичні проблеми, зокрема Чорнобиль на Фукусіма, тільки підкреслюють неможливість нехтування проблематикою тілесності та її трансформацій. Н.П. Дубовенко ФЕНОМЕН ТЕЛЕСНОСТИ И ЕЕ СОЦИОКУЛЬТУРНЫЕ РЕПРЕЗЕНТАЦИИ В УКРАИНСКОЙ И ЯПОНСКОЙ КУЛЬТУРЕ Человеческая телесность как социально-философская проблема постоянно привлекала интерес: как телесные силы раскрываются в жизни и в социальном бытии человека, какой есть взаимосвязь тела, души и духа и есть ли границы их развития. Феномен телесности и ее социокультурные репрезентации в украинской и японской культуре в достаточной мере новая и малоисследованная тема. Технократические проблемы, такие как Чернобыль и Фукусима, только подчеркивают невозможность пренебрежения проблематикой телесности и ее трансформаций. Ключевые слова: телесность, философия телесности, репрезентация тела, абстракция тела, тело-объект, тело-субъект, эстетизация тела. N. P. Dubovenko THE PHYSICALITY PHENOMENA AND ITS SOCIOCULTURAL REPRESENTATIONS IN UKRAINIAN AND JAPANESE CULTURES Human physicality as a socio-philosophical problem always attracted an interest: how exactly physical powers act in life and in social existence of a person, which is a bound between body, soul and spirit and are there any limits of their progress. The physicality phenomena and its sociocultural representations in Ukrainian and Japanese cultures is in fact a new and undeveloped theme. The technocratic problems such as Chernobil and Fucushima only point us to the fact, that we cannot neglect the problematic of physicality and its transformations. Keywords: physicality, philosophy of the physicality, body’s representation (representation of a body), abstraction of a body, object-body, subject-body, body’s esthetisation.